1743. Antimicrobial and Diagnostic Stewardship Targeting Urinary Tract Infections in the Emergency Department: A Pharmacist-driven Quality Improvement Project at a Tertiary Military Treatment Facility. (15th December 2022) - Ayalew, Memar; Admassu, Hellena; Ressner, Roseanne; Williams, Robin; Crull, Paulette; Brooks, Daniel
Abstract: Background: With the increasing interest in ambulatory stewardship, we designed a quality improvement project to enhance guideline concordant antimicrobial and diagnostic stewardship practices targeting urinary tract infections (UTI) in the ED of a Military Treatment Facility. Between two data collection phases (P1, P2), we provided education on national guidelines, local protocols and antibiograms, modified order-sets, and implemented enhancements targeting urine collection. The primary outcome was a change in guideline-concordant practices between P1 and P2. Methods: This prospective pharmacist-driven study had two 3-month data collection periods including ED encounters that resulted in a urinalysis (UA), urine culture (UCx) and antibiotics for UTI upon discharge. We collected data on participant demographics, clinical course and therapy details via chart review. Culture callback and corresponding interventions were made within 72 hours. Based on P1 results, we broadened our scope in P2 to include a diagnostic stewardship arm (Figure 1). This project was IRB approved under a non-research determination. Results: There were no significant changes in guideline-concordant prescribing or diagnostic practices between P1 and P2 (Figure 2). Inappropriate antibiotic selection was primarily due to use of cephalosporins and FQs as first line agents (Table 1). The primary pharmacy intervention was discontinuation of therapy (P1 29.1%, P2 39.8%). One-third of patients receiving antibiotics were asymptomatic, a majority of which had a positive UA (P1 68.4%, P2 73.3%). There was a high rate of UCx contamination which improved in P3 but did not reach statistical significance (P1 25.6%, P2 17.2%, p=0.19). Across all P2 encounters, 51.4% of UCx were deemed inappropriate. Conclusion: Significant guideline-discordant prescribing persisted despite interventions. An overreliance on UA findings results in treatment of asymptomatic bacteriuria. Education and order-set modification alone are insufficient for a lasting impact on prescribing practices especially where there is a high rate of provider turnover. An EMR with embedded clinical and alert-based decision support capabilities are likely to make a sustained impact in curbing inappropriate treatment of asymptomatic bacteriuria. Disclosures: All Authors : No reported disclosures.